Isolation and characterization of lytic Enterobacter cloacae phages associated with papaya dieback disease / Normy Idayu Esahak Ayub - Esahak Ayub, Normy Idayu (2024)
A search for an effective, green and safe method to control papaya dieback disease (PDD) associated Enterobacter cloacae in Malaysia which has resulted in economic losses to farmers motivates this research. Bacteriophages, the natural predator of bacteria could be the solution. Thus, the aims of this study were to isolate and identify lytic phages of E.cloacae associated with (PDD), determine their biological properties and stability to exposures to physical and chemical agents and evaluate their suitability as biocontrol agents for E.cloacae associated with plant diseases. Their presence was detected by plaque assay using the soft agar overlay method, followed by identification based on Transmission Electron Microscope morphology. The phage nucleic acid type was determined by RNaseA and DNaseI treatment. A one-step growth curve experiment was conducted to ascertain latent period and burst size. The host range was tested against various E. cloacae strains, bacterial soft rot of dragon fruits (BSRDF), banana wilt disease (BWD), clinical infections and other phytopathogens. Protein profiles of phages were determined by SDS-PAGE. Based on their latent period, burst size and stability at the different physical conditions their potential as biocontrol agent was evaluated. Of the nine lytic E. cloacae phages isolated, five (ECϕ1, ECϕ6, ECϕ7, ECϕ8, and ECϕ9) were further studied. All identified phages were DNA viruses, with ECϕ1, ECϕ8, and ECϕ9 belonging to the Myoviridae family, while ECϕ6 and ECϕ7 to the Inoviridae family. ECϕ1, ECϕ8, and ECϕ9 exhibited latent periods of 15 to 18 minutes and burst sizes ranging from 41 to 88 particles/cell. ECϕ6 and ECϕ7 had shorter latent periods of six and 12 minutes with burst sizes of two and six particles/cell. The host range of the phages are limited to E.cloacae strains from both plants and clinical origins. All the phages except ECϕ6 exhibited thermos-stability up to 60°C. All exhibited pH stability ranging from pH3 to pH10. ECϕ9 was least affected by exposure to UV and chloroform. Based on their protein profiles, two morphotypes were observed in each family. E.cloacae phages were successfully isolated and characterized with EC9 being evaluated as the most suitable biocontrol agent candidate for E.cloacae associated with PPD, BSRDF and BWD as well as with human infections.